Compressive Response of Non-slender Octet Carbon Microlattices - Kudo, Akira; Misseroni, Diego; Wei, Yuchen; Bosi, Federico (Frontiers in Materials, 2019)
Lattices are periodic three-dimensional architected solids designed at the micro and nanoscale to achieve unique properties not attainable by their constituent materials. The design of lightweight and strong structured solids by additive manufacturing requires the use of high-strength constituent materials and non-slender geometries to prevent strut elastic instabilities. Low slenderness carbon octet microlattices are obtained through pyrolysis of polymeric architectures manufactured with stereolithography technique. Their compressive behaviour is numerically and experimentally investigated when the relative density $\bar{ρ}$ ranges between 10$%$ and 50$%$, \textcolor{red}{with specific stiffness and strength approaching the limit of existing micro and nanoarchitectures}. It is shown that additive manufacturing can introduce imperfections such as increased nodal volume, non-cubic unit cell, and orientation-dependent beam slenderness, all of which deeply affect the mechanical response of the lattice material. An accurate numerical modelling of non-slender octet lattices with significant nodal volumes is demonstrated to overcome the limitations of classical analytical methods based on beam theory for the prediction of the lattice stiffness, strength and scaling laws. The presented numerical results and experimental methods provide new insights for the design of structural carbon architected materials towards ultra-strong and lightweight solids.